Odpowiedzi

Najlepsza Odpowiedź!
2010-02-01T21:05:00+01:00
C) 3 ( x - 2 ) - 5 x = 10
3x-6-5x=10
-2x=16
x=-8

d) ( 4 x - 5 ) - 2 ( x + 3 ) = - 9
4x-5-2x-6=-9
2x=2
x=1
  • Użytkownik Zadane
2010-02-01T21:06:45+01:00
3 (x-2)-5x=10
3x-6-5x=10
-2x=16/ : (-2)
x=-8

( 4 x - 5 ) - 2 ( x + 3 ) = - 9
4x-5-2x-6=-9
2x=-9+5+6
2x=2 /:2
x=1

liczę na naj mam nadzieję że pomogłam;));**

2010-02-01T21:10:57+01:00
3(x-2)-5x=10
3x-6-5x=10
3x-5x=10+6
-2x=16/:-2
x=-8

(4x-5)-2(x=3=-9
4x-5-2x-6=-9
4x-2x=-9+11
2x=2 /:2
x=1